PEMILIHAN MODEL EKONOMI EMPIRIK DENGAN PENDEKATAN KOREKSIKESALAHAN - Insukindro Insukindro (Journal of Indonesian Economy and Business (JIEB), 1999)
For the last two decades, one of the major development in dynamicspecifications has been an error correction model (ECM). The ECM can be motivatedby optimizing behavior of economic agents in the presence of disequilibrium in theeconomy. In this case, the agents need to optimize subjet to a separate disequilibriumand adjustment costs. The disequilibrium cost is the cost associated with being out oflong run equilibrium, whereas the adjustment cost is the cost associated with changesin the variables in question.This approach can not only capture the short- and long-run specifications andprovide an attractive statistical framework, but is also consistent with the concept ofcointegration or equilibrium relationships in economic time series. It has also beenwidely used to model the dynamic specifications in economic analysis, because it hasa number of advantages both in terms of its value in generating estimated regressionequations with desirable statistical properties and in term of the ease with which suchequations can be interpreted.